Charismatic Leadership and Job Performance: Mediation of Interpersonal Communication and Moderation of Leader Vision - Rafiq, Sahar; Khan, Muhammad Tasnim (Pakistan Journal of Humanities and Social Sciences, 2023)
The study investigates the association between charismatic leadership and job performance using interpersonal communication as a mediator and leader vision as moderator variables. The social cognitive theory uses as a theoretical lens to understand this conceptual framework. The sample of the study is those organizations that have undergone a central level of change. The study used a cross-sectional research design and data was collected from 350 participants through paper–and–pencil questionnaires to 30 different organizations. This exploratory study uses structural equation modeling (SEM) with common method bias (CMB), discriminant, and convergent validity tests to analyze the data. The results of this study explain how charismatic leadership impacted job performance with moderated (leader vision) mediation (interpersonal communication) analysis. These significant insights delineated practical as well as theoretical implications for both researchers and policymakers. This study significantly contributes to the body of knowledge on human resource literature. According to researchers’ knowledge, this study is one of the pioneer studies to investigate leader vision as a moderator variable between stated associations in the Pakistani context.